2017
DOI: 10.5194/acp-17-11655-2017
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of large-scale circulation on urban ambient concentrations of gaseous elemental mercury in New York, USA

Abstract: Abstract. The impact of large-scale circulation on urban gaseous elemental mercury (GEM) was investigated through analysis of 2008-2015 measurement data from an urban site in New York City (NYC), New York, USA. Distinct annual cycles were observed in 2009-2010 with mixing ratios in warm seasons (i.e., spring-summer) 10-20 ppqv ( ∼ 10-25 %) higher than in cool seasons (i.e., fall-winter). This annual cycle was disrupted in 2011 by an anomalously strong influence of the US East Coast trough in that warm season a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Sea-air exchange fluxes of Hg 0 in the SCS ranged (Fig. 9b and Table S3), which was comparable to the previous measurements obtained in the Mediterranean Sea, northern SCS, and western Atlantic Ocean (Andersson et al, 2007;Fu et al, 2010;Soerensen et al, 2013) but lower than those in polluted marine environments, such as Minamata Bay, Tokyo Bay, and the YS (Narukawa et al, 2006;Ci et al, 2011;Marumoto and Imai, 2015), while higher than those in some open sea environments, such as the Baltic Sea, Atlantic Ocean, and South Pacific Ocean (Kuss and Schneider, 2007;Kuss et al, 2011;Andersson et al, 2011;Soerensen et al, 2014). Interestingly, we found that the Hg 0 flux near station 99 was higher than those in open water as a result of higher wind speed (Table S3).…”
Section: Sea-air Exchange Of Hg 0 In the Scssupporting
confidence: 89%
See 1 more Smart Citation
“…Sea-air exchange fluxes of Hg 0 in the SCS ranged (Fig. 9b and Table S3), which was comparable to the previous measurements obtained in the Mediterranean Sea, northern SCS, and western Atlantic Ocean (Andersson et al, 2007;Fu et al, 2010;Soerensen et al, 2013) but lower than those in polluted marine environments, such as Minamata Bay, Tokyo Bay, and the YS (Narukawa et al, 2006;Ci et al, 2011;Marumoto and Imai, 2015), while higher than those in some open sea environments, such as the Baltic Sea, Atlantic Ocean, and South Pacific Ocean (Kuss and Schneider, 2007;Kuss et al, 2011;Andersson et al, 2011;Soerensen et al, 2014). Interestingly, we found that the Hg 0 flux near station 99 was higher than those in open water as a result of higher wind speed (Table S3).…”
Section: Sea-air Exchange Of Hg 0 In the Scssupporting
confidence: 89%
“…The DGM concentration in this study varied from 23.0 to 66.8 pg L −1 with a mean value of 37.1 ± 9.0 pg L −1 (Fig. 9a and Table S3), which was higher than those in other open oceans, such as the Atlantic Ocean (11.6 ± 2.0 pg L −1 , Anderson et al, 2011) and South Pacific Ocean (9−21 pg L −1 , Soerensen et al, 2014), but considerably lower than that in Minamata Bay (116 ± 76 pg L −1 , Marumoto and Imai, 2015). The mean DGM concentration in the northern SCS (41.3 ± 10.9 pg L −1 ) was significantly higher than that in the western SCS (33.5±5.0 pg L −1 ) (t test, p < 0.01).…”
Section: Sea-air Exchange Of Hg 0 In the Scsmentioning
confidence: 68%
“…Mercury (Hg) is a ubiquitous toxic metal of global concern, and the atmosphere is the major distribution medium for Hg cycling in the environment . Atmospheric Hg primarily exists as gaseous elemental mercury (GEM), which can be taken up directly by vegetation or converted to gaseous oxidized mercury (GOM) and particulate-bound mercury (PBM) and then deposited to aquatic and terrestrial ecosystems. , Toxic methylmercury is then formed in aquatic ecosystems and biomagnified along the food chain to influence human health through consumption of fish. , With a lifetime of about 0.5–1 year, GEM is transported globally via atmospheric circulation and considered a global pollutant. , Anthropogenic sources account for 30% of total Hg emissions into the atmosphere, while the remaining stems from natural sources (10%) and re-emission (60%), including ocean evasion, a major driver of global Hg cycling. , Climate is closely linked with ocean evasion and other routes associated with Hg re-emission, , where recent studies have even suggested that climatology effects could offset reduced primary anthropogenic Hg emissions by accelerating the cycling of Hg natural sources. , Therefore, physical variables associated with large-scale teleconnections should be considered when interpreting time series of atmospheric Hg. ,, …”
Section: Introductionmentioning
confidence: 99%